Regularities in propagation of opened corrosion‐induced cracks in concrete - Jokūbaitis, Vidmantas (Journal of Civil Engineering and Management, 2007)
Long and short‐term (accelerated with simulation of pressure developed by compressed rust) experimental investigations were accomplished. It was investigated in long‐term tests the relationship between the width of the longitudinal cracks on the concrete surface and close to the reinforcement, and relation between these widths and corrosion‐induced damages in the reinforcement; parameters of these relationships were established. In short‐time investigations it was tried to clarify the influence of transverse reinforcement and opened normal cracks on the nature of longitudinal cracks propagation. It has been determined that the character and the rate of propagation of the longitudinal cracks depend on distribution of transverse reinforcement and normal cracks along a member. Armatūros korozijos atsivėrusių betono plyšių plitimo dėsningumai Armatūros korozijos atsivėrusių betono išilginių plyšių plitimui analizuoti atlikti ilgalaikiai ir trumpalaikiai (paspartinti, imituojant suslėgtųjų rūdžių slėgį) eksperimentiniai tyrimai. Ilgalaikiuose bandymuose buvo tiriama išilginio plyšio pločio betono paviršiuje ir prie armatūros tarpusavio priklausomybė ir šių pločių bei armatūros korozinių pažaidų ryšys; nustatyti šių priklausomybių parametrai. Trumpalaikiais tyrimais buvo siekiama nustatyti, kokią įtaką išilginių plyšių plitimo pobūdžiui turi gelžbetoninio elemento skersinė armatūra ir atsivėrę normaliniai plyšiai. Nustatyta, kad nuo skersinės armatūros ir normalinių plyšių tarpusavio išsidėstymo išilgai elemento priklauso išilginių plyšių plitimo braižas ir greitis. Reikšminiai žodžiai: korozija, rūdžių sluoksnis, plyšiai, skersinė armatūra. First Published Online: 14 Oct 2010